Sewage sludge conditioning using cationic, anionic and non-ionic polymers - Wai, Kien Tat; Saed, Katayon; Megat Mohd Noor, Megat Johari; Idris, Azni; Muyibi, Suleyman Aremu (Federation of Engineering Institutions of Islamic Countries, 2006)
The present study was carried out to evaluate the effectiveness of the synthetic polymers; cationic (Praestol 852 BC), anionic (Praestol 2530) and non-ionic polymer (Praestol 2500) in enhancing dewaterability of sewage sludge. Sewage sludge samples were collected from holding tank. The optimum operational conditions for the sewage sludge conditioning for each polymer were carried out in terms of mixing speed, mixing duration and dosages of polymer. Changes in Capillary Suction Time (CST), Specific Resistance to Filtration (SRF) and zeta potential (Zeta Potential) were monitored to assess the effectiveness of each polymer. For cationic polymer, the optimum conditions were obtained when mixing duration were in the range of 3 to 4 minutes, polymer dosages were between 5 and 7 mg/L and mixing speed in the range of 160 to 200 rpm. The optimum conditions for anionic polymer for mixing speed, mixing duration and dosages of polymer were in the range of 100 to 200 rpm, 3 to 5 minutes and 2 to 3.5 mg/L, respectively. Lower CST and SRF values for the sludge conditioned using cationic polymer as compared to anionic polymer revealed that cationic polymer was more effective in terms of dewaterability enhancement. Non-ionic polymer definitely was not a suitable conditioner for the sewage sludge conditioning. Increment in zeta potential value was observed as the dosage of cationic polymer increased. However, in the case of anionic polymer, an inverse relationship between zeta potential values and polymer dosage was recorded. Prediction of CST, SRF and ZP values using cationic and anionic polymers under the optimum conditions could be done using established equations as designed by Minitab and were comparable with values obtained from experiment.